2017
DOI: 10.1016/j.amjmed.2017.05.049
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 and 2 Myocardial Infarction and Myocardial Injury: Clinical Transition to High-Sensitivity Cardiac Troponin I

Abstract: cTnI increases are encountered in approximately a third of patients, the majority due to nonatherothrombotic conditions. Compared with patients without myonecrosis, type 2 myocardial infarction and myocardial injury have worse short-term outcomes, with mortality rates >20% at 2 years. hs-cTnI assay does not lead to more myocardial injury or infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
79
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(93 citation statements)
references
References 18 publications
5
79
1
2
Order By: Relevance
“…The baseline clinical characteristics and treatment of patients with T2MI are summarized in Table . The mean age of patients with T2MI was over 60 years; most studies revealed that the percentage of male patients ranged from 52.8% to 98.6% in patients with T2MI, but the studies of Szymariski et al, Sandoval et al, and Arora et al found percentages of female patients of 60.3%, 59%, and 51.9%, respectively .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The baseline clinical characteristics and treatment of patients with T2MI are summarized in Table . The mean age of patients with T2MI was over 60 years; most studies revealed that the percentage of male patients ranged from 52.8% to 98.6% in patients with T2MI, but the studies of Szymariski et al, Sandoval et al, and Arora et al found percentages of female patients of 60.3%, 59%, and 51.9%, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…The baseline clinical characteristics and treatment of patients with T2MI are summarized in Table 1. 4,[12][13][14][15][16][17][18][19][20][21][22][23][24] The mean age of patients with T2MI was over 60 years; most studies revealed that the percentage of male patients ranged from 52.8% to 98.6% in patients with T2MI, found percentages of female patients of 60.3%, 59%, and 51.9%, respectively. 17,18,24 The ratio of patients with T2MI presenting with non-ST segment elevation myocardial infarction (NSTEMI) ranged from 70.1% to 97.5% (mean value: 87.1%); all studies found that patients with T2MI often had previous relevant medical history, but EI-Haddad et al did not describe medical history findings.…”
Section: Resultsmentioning
confidence: 99%
“…B. eine Aortenklappenstenose vorliegen können [6]. Unter diesem Aspekt ist es beunruhigend, dass gerade diese Patienten im Vergleich zur Kohorte mit Typ-I-MI in geringerem Maße medikamentöse Prävention hinsichtlich des kardiovaskulären Risikoprofils erhalten [11] auch weil sich in dieser heterogenen Gruppe etliche Patienten mit primär niedrigerer Prätestwahrscheinlichkeit für eine koronare Herzerkrankung befinden.…”
Section: Kur Zgefasstunclassified
“…10,29 Rates of obstructive CAD in T2MI patients undergoing coronary angiography range from 28% to 78%. 3,8,9,27 Despite a high prevalence of CAD in these patients, significant disparities exist in medical management of even those with CAD in T2MI or myocardial injury, when compared with those with T1MI 1,3,4,[8][9][10][11][12]14,15,[19][20][21][22][23][24][25][26][27] (Table 2).…”
Section: Introductionmentioning
confidence: 99%